Estuarine sediment resuspension and acidification: Release behaviour of contaminants under different oxidation levels and acid sources. (1st September 2017) - Martín-Torre, M. Camino; Cifrian, Eva; Ruiz, Gema; Galán, Berta; Viguri, Javier R.
Abstract: Carbon dioxide (CO2 ) Capture and Storage (CCS) is a technology to reduce the emissions of this gas to the atmosphere by sequestering it in geological formations. In the case of offshore storage, unexpected CO2 leakages will acidify the marine environment. Reductions of the pH might be also caused by anthropogenic activities or natural events such as acid spills and dredging operations or storms and floods. Changes in the pH of the marine environment will trigger the mobilisation of elements trapped in contaminated shallow sediments with unclear redox boundary. Trace element (As, Cd, Cr, Cu, Ni, Pb and Zn) release from anoxic and oxic estuarine sediment is analysed and modelled under different laboratory acidification conditions using HNO3 (l) and CO2 (g): acidification at pH = 6.5 as worst-case scenario in events of CO2 leakages and acid spills, and acidification at pH = 7.0 as a seawater scenario under CO2 leakages, acid spills, as well as sediment resuspension. The prediction of metal leaching behaviour appear to require sediment specific and site specific tools. In the present work it is demonstrated that the proposed three in-series reactions model predicts the process kinetics of the studied elements under different simulated environmental conditions (oxidation levels and acid sources). Differences between HNO3 and CO2 acidification are analysed through the influence of the CO2 gas on the ionic competition of the medium. The acidification with CO2 provokes higher released concentrations from the oxic sediment than from the anoxic sediment, except in the case of Zn, which influences the release of the other studied elements. Slight acidification can endanger the aquatic environment through an important mobilisation of contaminants. The obtained prediction of the contaminant release from sediment (kinetic parameters and maximum concentrations) can contribute to the exposure assessment stage for risk management and preincidental planning in accidental CO2 leakages and chemical spills scenarios. Graphical abstract: Highlights: Trace element release under resuspension conditions from anoxic and oxic sediment. Experimental and modelled release under HNO3 and CO2 conditions at pH = 6.5. CO2 acidification enhances contaminant mobility under slightly acidic scenarios. The sediment resuspension mobilises more Pb than acidification at pH = 7.0.